PROMOTIONAL STRATEGY ANALYSIS IN IMPROVING THE ROOMS IN ZODIAK HOTEL KEBON KAWUNG - Taufansyah Firdaus; Indah Nur Agustiani; I Made Dwipa Agastya (Faculty of Economics and Business, University of Pasundan, 2018)
This research aims to analyze the appropriate promotional strategies in increasing the occupancy of the Zodiak Kebon Kawung Hotel Bandung. 15 respondents were taken as a sample of research using purposive sampling from employees of executive sales and executive e-commerce at Zodiak Kebon Kawung Hotel. The analysis used is a SWOT analysis consisting of internal factor analysis factor (IFAS) matrix, external factor analysis summary (EFAS) matrix, external-internal matrix (IE), cartesian diagram and SWOT matrix. These are the position of growth strategy with IFAS score = 2.21, EFAS = 2.50, dan SWOT Matrix; 1) SO strategy ie accessibility of adequate means of transportation, modern hotels; 2) ST strategy that is not expensive and supported by security; 3) WO Strategy that is to improve human resources, facilities and infrastructure of water and sewage treatment, improvement of in-room facilities; 4) WT strategy is to avoid the transfer of educated and experienced personnel.